FORMING A SCIENTIFIC WORLDVIEW OF FUTURE TEACHERS THROUGH INDEPENDENT THINKING - Kholmatova Ziroat Anvarovna (Web of Journals Publishing, 2024)
This article presents the pedagogical conditions for forming a scientific worldview of future teachers through independent thinking, its scientific substantiation, the use of interactive educational technologies in the educational process and some considerations on the formation of a scientific worldview on this basis.
Keywords: Independent thinking, scientific worldview, interactive education, modern methods, creativity, critical approach, teacher, development.